Pharmacoeconomic study of the effectiveness of cytogenetic studies in patients with MM before prescribing first-line therapy - Yu. A. Zabolotneva; I. S. Krysanov (Izdatelstvo OKI, 2024)
Purpose of the study. Conducting an assessment of the economic consequences (clinical and economic analysis) when conducting cytogenetic studies before prescribing various first-line treatment regimens for multiple myeloma (MM). Materialsand methods. The pharmacoeconomic study was carried out using the method of cost analysis, "cost-effectiveness" within the framework of the State Guarantee Program (SGP). Results. A review of the literature demonstrated that a limited number of data are currently available on the clinical effectiveness of the analyzed regimens in the first line, both in patients with normal and high cytogenetic risk. The cost-effectiveness analysis showed that among the three studied 1st-line treatment regimens (VMP, Rd, VRd), in terms of PFS (progression-free survival), the coefficient was minimal for the VMP regimen in patients with high cytogenetic risk. Conclusion. The study showed that the choice and prescription of first-line therapy, depending on the results of a cytogenetic study, is a clinically effective and cost-effective approach to organizing medical care for adult patients with multiple myeloma in the Russian Federation. This could be used in the future to formulate.